A Comparative Study Of Enhanced Nonlinear PI To Multivariable Nonlinear Plant - Samsudin, Sharatul Izah; Sulaiman, Noor Asyikin; Md Yusop, Azdiana; M. Salim, Sani Irwan (Penerbit Universiti,UTeM, 2018)

(untitled)
The static gains of PI controller have limitation to handle the process nonlinearities of the system.This suggests the development of enhanced nonlinear PI controller where a nonlinear gain function is cascaded to PI parameters.Two nonlinear gain functions are developed and the effectiveness of the control performance is investigated for two different control structures for a multivariable nonlinear wastewater treatment plant (WWTP).It was proved that superior output with the lower mean error was obtained by developed nonlinear PI specifically in the multivariable control structure.The developed nonlinear PI offers simpler control structure and easy implementation hence offering alternative control strategy for the multivariable system.